Problems of social adaptation of young people at the market of labour (Journal of Economic Research & Business Administration, 2015)
Youth – is the most vulnerable social and demographic group of the population on a labor market as doesn't possess sufficient vocational training and labor skills. In this regard, more and more notable characteristic of economic-social situation of youth is growth of unemployed number in this environment. Sharply there is a problem of school, college and higher educational institutions graduates' employment because many of them receive free distribution. Success of youth adaptation in a professional and labor field is connected with realization of innovative model of adaptation and this innovative model during which the youth carries out professional subjectivity as stage-by-stage alternation of stages, connected with choice of profession and professional formation in the course of labor activity, with continuous education as "education during life". Need of continuous education during life is dictated at the present stage by information revolution and increase of knowledge role, need for continuous updating of knowledge, but "live" knowledge, capable to development and modification, transformation.
Keywords: tourism; tourism objects; purposes of tourism trips; adaptation strategies; problems of tourism